Depression Intensity in Patients with Schizophrenia - Zoja Babinkostova; Branislav Stefanovski; Silvana Naunova-Timovska (ID Design 2012, 2011)
Background: Depressive symptoms are common in schizophrenia and they can occur during any phase of the disorder. Previous studies indicate that depression in schizophrenic patients is generally with mild or moderate intensity. Aim: We undertook this study with the aim of evaluation of the presence and intensity of the depressive symptoms in patients with schizophrenia. Material and Methods: The examined group consisted of 50 patients with schizophrenic disorder, both inpatients and outpatients treated at the University Clinic of Psychiatry, who had prominent depressive symptoms (total score >7 on 17-item Hamilton Depression Rating Scale). The control group consisted of 50 patients with depressive disorder. Differential diagnosis was established on the basis of ICD-10 diagnostic criteria. Patients were evaluated with PANSS, 17-item Hamilton Depression Rating Scale (HAMD) and a questionnaire for demographic and clinical data. Results: The percentage of patients with depressive symptoms among the patients with schizophrenic disorder was 54 %. Schizophrenic patients more frequently presented mild and moderate depression in comparison to the control group in which moderate and severe depression were more frequent. Conclusion: Patients with schizophrenia more frequently present mild and moderate depression.
Keywords: schizophrenia; depressive disorder; depression intensity